An Overview of Key Soil Nitrogen Cycling Transformations - Clayton J Nevins; Sarah L Strauss; Patrick Inglett (EDIS, 2020)
Although nitrogen (N) is one of the most abundant elements in the biosphere, it is generally at levels that are limiting for optimum plant growth and crop production in Florida soils. To maintain adequate N levels in Florida soils without having detrimental environmental side effects, one must understand and manage N cycling transformations and processes. This new 5-page article, published by the UF/IFAS Department of Soil and Water Sciences, provides an overview of the N cycle by describing key N transformations that result in soils gaining or losing N. The biotic and abiotic processes that govern these transformations are described, as well as practical examples of these transformations in Florida soils. Written by Clayton J. Nevins, Sarah L. Strauss, and Patrick Inglett. https://edis.ifas.ufl.edu/ss684